Responses of grain zinc and nitrogen concentration to nitrogen fertilizer application in rice varieties with high-yielding low-grain zinc and low-yielding high grain zinc concentration - Pennapa Jaksomsak (2018)
© 2016, Springer International Publishing Switzerland. Background and aims: Rice crop management for Zn biofortification should also benefit yield. This study established how grain Zn concentration and yield of rice varieties with a range of grain Zn concentration vary under different N-fertilizer applications. Methods: Rice varieties, the low-yield/high grain Zn varieties KPK and NR, the high-yield/medium grain Zn variety KDML105 and the high-yield/low grain Zn varieties CNT1 and RD21, were grown under field conditions with fertilizer rates of 60 and 120 kg N ha −1 . Results: Increasing N rate increased grain Zn concentration and yield in the high-yield/low grain Zn varieties, but depressed grain Zn concentration and increased grain yield in the low-yield/high grain Zn varieties. On the other hand, it increased grain N in all five varieties. Grain Zn concentration was associated positively with yield and grain N concentration in low grain Zn concentration varieties, but negatively in high-grain Zn varieties. Conclusions: Nitrogen fertilizer increased grain Zn concentration and yield simultaneously in low-grain Zn varieties, but depressed grain Zn concentration, while boosting yield, in high-grain Zn varieties.